Development of Guided Inquiry based on Blended Learning (GIbBL) Teaching Module for Physics in the Independent Curriculum - Herliana, Fitria; Kasli, Elisa; Azhariah, Siti Kalsuma; Mahzum, Elmi; Farhan, Ahmad; Nurulwati, Nurulwati; Syukri, Muhammad; Mohtar, Lilia Ellany (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2023)
This study aims to develop a teaching module with a guided inquiry model based on blended learning (GIbBL) that can be applied in the independent curriculum. This kind of research uses the ADDIE development paradigm, which consists of the following steps: 1) Analysis, 2) Design, (3) Development, 4) Implementation, and 5) Evaluation. Due to time constraints, the teaching module in this study was only develop to the development stage. The feasibility of the teaching modules was assessed through expert validation tests and practicality tests, which involved gathering responses from research subjects. The subjects of this study were physics teachers and students of class XI SMAN 7 Banda Aceh. The data collection technique employed in this study utilized a questionnaire instrument, comprising a material and learning design expert validation questionnaire, as well as a teacher and student response questionnaire. Data analysis involved percentage descriptive analysis. The results of the material expert validation test demonstrated a percentage of 93,25%, while the learning design expert validation test yielded 91,5%, both falling within the